2021
DOI: 10.1097/cce.0000000000000310
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Sedation for Acute Respiratory Distress Syndrome Patients on Venovenous Extracorporeal Membrane Oxygenation and Ultraprotective Ventilation

Abstract: Objectives: Patients on extracorporeal support for severe acute respiratory distress syndrome may require a prolonged period of deep sedation. In these patients, volatile sedation may represent a valid alternative to IV drugs. The aim of our study was to describe the feasibility of volatile sedation in a large cohort of acute respiratory distress syndrome patients undergoing venovenous extracorporeal membrane oxygenation and ultraprotective ventilation. Design: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Ferrando et al observed that the use of sevo urane resulted in a greater immunosuppressive effect than propofol, with less alteration in the permeability of alveolar capillaries and consequent improvement in oxygenation [31]. The use of halogenated anesthetics has also shown bene ts in patients with ARDS undergoing extracorporeal membrane oxygenation (ECMO) [32].…”
Section: Discussionmentioning
confidence: 99%
“…Ferrando et al observed that the use of sevo urane resulted in a greater immunosuppressive effect than propofol, with less alteration in the permeability of alveolar capillaries and consequent improvement in oxygenation [31]. The use of halogenated anesthetics has also shown bene ts in patients with ARDS undergoing extracorporeal membrane oxygenation (ECMO) [32].…”
Section: Discussionmentioning
confidence: 99%
“…This study showed increased depth of sedation with isoflurane, reduced need for opiates and neuromuscular blockade, less adverse effects, and similar outcomes when compared to intravenous (iv) sedation with midazolam or propofol. 27 Although these findings are exploratory, volatile sedation may be a future feasible therapeutic alternative for patients receiving ECMO for ARDS. 27 Although the lack of propofol-associated HTG complications demonstrated in our study could be attributed to the prompt discontinuation of propofol in approximately 51.7% of patients, and reduction in rate in 29.3% of patients, another possible conclusion remains that propofol-associated pancreatitis, even in the setting of HTG, is rare in congruence with published literature.…”
Section: Discussionmentioning
confidence: 99%
“…The coordination of care in this case was complex, and the time spent by multiple providers, both in consultation with each other and individually, would likely limit the possibility of isoflurane delivery becoming a common practice. Anesthetic delivery systems that administer volatile anesthetics directly into endotracheal tubes have been developed and are being researched for the delivery of anesthetics to invasively ventilated patients ( 22 ). In a retrospective study of 74 patients, Grasselli et al found that inhaled volatile anesthetic (isoflurane) delivered via the inhalation route using one of these anesthetic delivery systems can be a safe alternative to continuous IV sedation in patients on VV ECMO for ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple postulated mechanisms regarding how these agents work, including direct relaxation of bronchial smooth muscle, inhibition of the release of inflammatory mediators, beta adrenergic receptor stimulation, reduction of vagal tone and vagal-mediated reflexes and antagonism of the effects of histamine and methacholine (19)(20)(21). The use of inhaled anesthetics in patients requiring ECMO has been reported more recently, both in severe refractory SA and acute respiratory distress syndrome (ARDS) (19,22); however, the literature is limited. In previously reported cases of utilization of inhaled volatile anesthetics for severe SA, the anesthetics were delivered via the inhalational route utilizing an anesthesia ventilator (19,23).…”
Section: Advanced Therapies For Status Asthmaticusmentioning
confidence: 99%